WEAVING REALITY AND MUSLIM IDENTITY - Nurhasanah, Siti; Nugraha, Mulyawan Safwandy (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2025)
This study investigates the factors influencing the formation of Muslim identity among students at Najib Bariq Islamic Junior High School. The research discusses how the role of the family affects the religious identity of students. Limited funding at the school results in restricted extracurricular activities, even though these activities are necessary for developing students' interests and talents beyond academic subjects. The influence of social media and mobile games is also discussed to show how these can distract students from their educational goals. The study aims to highlight the presence of a supportive school environment, structured learning programs, and non-formal activities in enhancing the formation of Muslim identity. Additionally, it addresses ways to overcome the impact of technology and contemporary challenges in instilling Islamic values in education. The findings emphasize a holistic educational approach that integrates Islamic values and meets the needs of today’s society. In this context, it demonstrates that collaboration between schools and families is crucial to prepare students to face modern challenges with a strong self-awareness as Muslims.